An Assay to Determine Mechanisms of Rapid Autoantibody-Induced Neurotransmitter Receptor Endocytosis and Vesicular Trafficking in Autoimmune Encephalitis - Amedonu, Elsie; Brenker, Christoph; Barman, Sumanta; Schreiber, Julian A.; Becker, Sebastian; Peischard, Stefan; Strutz-Seebohm, Nathalie; Strippel, Christine; Dik, Andre; Hartung, Hans-Peter; Budde, Thomas; Wiendl, Heinz; et al. (Frontiers in Neurology, 2019)
N-Methyl-D-aspartate (NMDA) receptors (NMDARs) are among the most important excitatory neurotransmitter receptors in the human brain. Autoantibodies to the human NMDAR cause the most frequent form of autoimmune encephalitis involving autoantibody-mediated receptor cross-linking and subsequent internalization of the antibody-receptor complex. This has been deemed to represent the predominant antibody effector mechanism depleting the NMDAR from the synaptic and extra-synaptic neuronal cell membrane. To assess in detail the molecular mechanisms of autoantibody-induced NMDAR endocytosis, vesicular trafficking, and exocytosis we transiently co-expressed rat GluN1-1a-EGFP and GluN2B-ECFP alone or together with scaffolding postsynaptic density protein 95 (PSD-95), wild-type (WT), or dominant-negative (DN) mutant Ras-related in brain (RAB) proteins (RAB5WT, RAB5DN, RAB11WT, RAB11DN) in HEK 293T cells. The cells were incubated with a pH-rhodamine-labeled human recombinant monoclonal GluN1 IgG1 autoantibody (GluN1-aAbpH-rhod) genetically engineered from clonally expanded intrathecal plasma cells from a patient with anti-NMDAR encephalitis, and the pH-rhodamine fluorescence was tracked over time. We show that due to the acidic luminal pH, internalization of the NMDAR-autoantibody complex into endosomes and lysosomes increases the pH-rhodamine fluorescence. The increase in fluorescence allows for mechanistic assessment of endocytosis, vesicular trafficking in these vesicular compartments, and exocytosis of the NMDAR-autoantibody complex under steady state conditions. Using this method, we demonstrate a role for PSD-95 in stabilization of NMDARs in the cell membrane in the presence of GluN1-aAbpH-rhod. Moreover, our data point towards a possible role for RAB proteins in the vertical trafficking of the internalized NMDAR-autoantibody complex in this heterologous expression system as suggested also for neuronal cells. This novel assay allows unraveling molecular mechanisms of autoantibody-induced receptor internalization in autoimmune encephalitis syndromes.